الإعلام البيئي والبيئة الإعلامية الجديدة: قراءة في خصائص الإعلام البيئي - بريك، الزهرة Brik, Alzahrah (جامعة الجزائر - معهد علوم الإعلام والإتصال, 2019)
تتناول هذه الدراسة موضوع الإعلام البيئي والبيئة الإعلامية الجديدة، حيث تسعى إلى إبراز أهمية البيئة والإعلام البيئي عبر وسائل الإعلام المختلفة، ونظرا لأن وسائل الإعلام الجديدة أصبحت متغلغلة في المجتمع وشديدة الالتصاق بأفراده، أصبح استخدام هذه الوسائل لنشر ثقافة الوعي البيئي من بين الضرورات الملحة، من هنا تهدف هذه الدراسة إلى إبراز كيفية توظيف الإعلام البيئي عبر وسائل الإعلام الجديدة من خلال تبيان طبيعة البيئة الإعلامية الجديدة وخصائص مضمون الإعلام البيئي بها. This study deals with the subject of environmental media and the new media environment, it seeks to highlight the importance of the environment and environmental media through various media, since new media have become permeated in society and highly attached to its members, the use of these media to spread a culture of environmental awareness has become an urgent necessity. From here, this study aims to highlight how environmental media is employed through new media by demonstrating the nature of the new media environment and the characteristics of the content of environmental information.
Keywords: علوم الإعلام والاتصال -- وسائل الإعلام -- الإعلام البيئي -- الوعي البيئي